If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -4 = 6x + 14 Reorder the terms: -4 + 8x = 6x + 14 Reorder the terms: -4 + 8x = 14 + 6x Solving -4 + 8x = 14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 8x + -6x = 14 + 6x + -6x Combine like terms: 8x + -6x = 2x -4 + 2x = 14 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + 2x = 14 + 0 -4 + 2x = 14 Add '4' to each side of the equation. -4 + 4 + 2x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 14 + 4 2x = 14 + 4 Combine like terms: 14 + 4 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| 6x-2=4x+4 | | -12x+9+24x+4=43 | | 0=-3y^2+7y+6 | | x-1=8x-8 | | 3(-2x+4)+5(4x-3)=4(-5x-2) | | 9x-3=4x-1 | | 7x-5=4x+7 | | =0.1428571429m+-0.4285714286y | | -(5y+5)-(-4y-7)=-1 | | 4(3x-7)-5(4x-2)= | | 7x+7=9x-9 | | 23x+67=55x-40 | | x^2+4x+6=10 | | 54*4= | | x+57,x=3 | | 4.39(5)+3.42N=76.11 | | 8x+2=7(x-4)+8 | | 6-5y=7-6y | | 2x+4=-7(-7x+6) | | 8y+2=7y-4 | | .6u-7=9-.6u | | 5-5x+8+2x+4x-2=6+4*3 | | 1.12a=149000000 | | 7g+5=12g-25 | | 6p-(5p-5)=-8-2(p+12) | | 3x^4(7x^3-4x-1)= | | .25+9=10-.75r | | 5x(1-x)=5(x-2) | | 6x^2-7x-20=(2x-5)(3x+4) | | x(2x-3)=35 | | z^4+2z^2-4z=0 | | 8+4x-12-2x=8 |